The Harmony of Sharia and Tradition: A Study of Islamic Da’wah Values ​​in the Pa'bitte Passapu Dance of the Ammatoa Community - Zulkarnaini Umar; Sonia Isna Suratin; Iman Asroa B.S (Center for Research and Development of Religious Literature and Heritage, 2024)
This study explores the integration of Islamic law (sharia) and local customs through the analysis of the Pa'bitte Passapu dance, a cultural expression of the Ammatoa community in Tanah Toa Village, Kajang District. Utilizing field research and Roland Barthes' cultural semiotic theory, this research reveals the denotative and connotative symbols within the dance movements. Data collection methods included observation, interviews, and documentation. The subjects of this study were the dancers of the Pa'bitte Pasapu dance, their trainers, and local government officials. The findings indicate that the Pa'bitte Passapu Dance embodies elements of harmony between sharia and da'wah, guiding society towards harmonious living. Denotatively, the dance features physical movements and visual symbols, such as spinning movements, fighting simulations, and the use of symbolic elements like chickens, which are part of the aesthetic performance. Connotatively, the dance conveys complex messages encompassing moral, social and ideological values. The study argues that the Pa'bitte Passapu Dance serves as a medium that connects sharia and art, providing entertainment while also reinforcing cultural identity and religious values within the Ammatoa community. This research highlights the importance of preserving local cultural expressions as a relevant and adaptive platform for preaching, while at the same time addressing local communities’ needs